The Use of Information Technology and Hospital Information Systems: A Study on Health Employees - Işık, Oğuz; Akbolat, Mahmut (Information World, 2010)
The aim of this study is to demonstrate the skills of using information technologies and hospital information systems of health employees and to evaluate their ideas about benefits of hospital information systems. Study was implemented in 11 hospitals operating in Sakarya on April 2009. 544 health employees have participated in the research. Data were collected by questionnaires. Descriptive statistical methods, independent sample t test and One Way ANOVA test were used to analyze the data. Reliability of the survey was calculated by using of Cronbach’s alpha coefficient. Results were assessed in a 95% confidence interval, p
Keywords: Hospital information system; Information technology; Health employees